Characterizing Cerebral Imaging and Electroclinical Features of Five Pseudohypoparathyroidism Cases Presenting with Epileptic Seizures - Zijuan Qi; Zhensheng Li; Quwen Gao; Li Dong; Jian Lin; Kairun Peng; Wei Xiang; Bingmei Deng (Behavioural Neurology)
Objective. To characterize the cerebral imaging and electroclinical features and investigate their etiological contributions to seizures in pseudoparathyroidism (PHP). Methods. The clinical symptoms, biochemical imaging by magnetic resonance imaging (MRI) and computed tomography (CT) tests, and electroencephalogram (EEG) manifestations of five PHP patients with seizures were retrospectively collected and analyzed. Results. Physical examination showed an average stature in cases 2~4 and short stature in cases 1 and 5. X-ray tests suggested ectopic calcification in four patients. The seizures in four cases were effectively controlled with antiseizure medicines (ASMs). Cerebral CT scans showed extensive brain calcifications in the bilateral basal ganglia (all five cases), cerebellum (cases 1, 3, and 5), thalamus (case 4), and cerebral cortex. Cerebral MRI showed short T1 signals mainly in the basal ganglia. EEG records revealed focal EEG abnormalities, including abnormal slow waves and epileptiform discharges, mainly over the temporal and frontal lobes. The brain areas with focal EEG abnormalities and calcification did not always coincide. Conclusion. The seizures in PHP can be focal to bilateral tonic–clonic. ASMs are effective in epilepsy combined with PHP. Intracranial calcification is not a reliable etiological cause of epilepsy in PHP patients.